2019
DOI: 10.1074/jbc.ra118.001907
|View full text |Cite
|
Sign up to set email alerts
|

Methionine oxidation in α-synuclein inhibits its propensity for ordered secondary structure

Abstract: Edited by Karen G. Fleming ␣-Synuclein (AS) is an intrinsically disordered protein highly expressed in dopaminergic neurons. Its amyloid aggregates are the major component of Lewy bodies, a hallmark of Parkinson's disease (PD). AS is particularly exposed to oxidation of its methionine residues, both in vivo and in vitro. Oxidative stress has been implicated in PD and oxidized ␣-synuclein has been shown to assemble into soluble, toxic oligomers, rather than amyloid fibrils. However, the structural effects of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…This effect was not only reported for aSyn, but also for other amyloidogenic proteins, such as AB and γ-synuclein (gSyn) 16 , 61 , 62 . Such effects are in agreement with the proposed mechanism of action for EGCG, whereby it mediates the reorientation of bonds between ordered protein molecules, leading to amyloid remodeling and the appearance of unordered, amorphous protein aggregates 17 , 63 . Additionally, similar results to those obtained here for anle138b and EGCG were obtained for the aggregation inhibitor SynuCleanD, which decreases aSyn aggregation in H4 neuroglioma cells.…”
Section: Discussionsupporting
confidence: 88%
“…This effect was not only reported for aSyn, but also for other amyloidogenic proteins, such as AB and γ-synuclein (gSyn) 16 , 61 , 62 . Such effects are in agreement with the proposed mechanism of action for EGCG, whereby it mediates the reorientation of bonds between ordered protein molecules, leading to amyloid remodeling and the appearance of unordered, amorphous protein aggregates 17 , 63 . Additionally, similar results to those obtained here for anle138b and EGCG were obtained for the aggregation inhibitor SynuCleanD, which decreases aSyn aggregation in H4 neuroglioma cells.…”
Section: Discussionsupporting
confidence: 88%
“…The intermediate 8+ ion will be used here as a representative state in order to monitor shifts in the conformational ensemble upon metal ion binding. The 8+ charge state demonstrates a characteristic pattern with four prominent conformational families in the CCS range of 2200-3000 Å 2 , which have been described before 52 .…”
Section: Resultssupporting
confidence: 63%
“…Noteworthily, also the inhibition of fibrillation of α-synuclein is mediated by methionine oxidation. It has been suggested that α-synuclein completely oxidized to its Met residues shows a reduced propensity to form amyloid fibrils, probably related to the interference of MetSO residues in oxidized protein to form ordered β-type secondary structures [51].…”
Section: Discussionmentioning
confidence: 99%